2000
DOI: 10.1046/j.1440-1673.2000.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

The rate of breast‐conserving surgery in early breast cancer: An audit of surgical practice at St Vincent’s campus, NSW in 1990 and 1994

Abstract: An audit was undertaken to document the use of breast-conserving surgery (BCS) in the management of early breast cancer (EBC) at St Vincent's campus during two time periods, the calendar years 1990 and 1994. The medical records of all women diagnosed with a new primary breast cancer at St Vincent's Public and Private Hospitals initially treated during 1990 and 1994 were reviewed to document patient, tumour and treatment characteristics. Comparisons were made with data on BCS in EBC from the Australian medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…At the time of initial surgical decision‐making for early breast cancer, a woman is not only confronted by the diagnosis of malignancy but also has to interpret information regarding choice between breast conservation and mastectomy 12 . The rate of mastectomy has been shown to vary not only between regions but also have significant surgeon dependence 4,5 . Presumably this is related to the ways that the options between breast conservation and mastectomy are discussed with the patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the time of initial surgical decision‐making for early breast cancer, a woman is not only confronted by the diagnosis of malignancy but also has to interpret information regarding choice between breast conservation and mastectomy 12 . The rate of mastectomy has been shown to vary not only between regions but also have significant surgeon dependence 4,5 . Presumably this is related to the ways that the options between breast conservation and mastectomy are discussed with the patient.…”
Section: Discussionmentioning
confidence: 99%
“…In 1990 the US National Institute of Health Breast Cancer Consensus Conference declared that breast conservation therapy (BCT, the use of breast preserving surgery and radiation therapy) was the optimal local therapy for the majority of women with early breast cancer 1 . Despite this recommendation and the subsequent meta‐analyses of clinical studies, which have confirmed the equivalent local control and survival of BCT compared to mastectomy 2,3 , the audits of BCT suggest the technique remains underutilized in the community 4–6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Canadian study, the rate of BCS increased between 1981 and the early 1990s 19 . One New South Wales study showed that the BCS rates were 33 and 36% for 1990 and 1994, respectively, in a large public hospital 20 . There was a marginal increase in BCS use in Victoria from 63% in 1995 to 69% in 1999 21 .…”
Section: Discussionmentioning
confidence: 99%